On A. D. Gordon’s “Ha’Arachat Atzmenu”: An Unpublished Essay Section about the Importance of Positive Religious Sentiments toward Judaism to the Realization of Zionism (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2026)
How is emotional estrangement from the religion of Israel a deterrence to the realization of the goals of Jewish nationalism? Yael Gordon's private archive contains her father, Aharon David Gordon's, manuscript. The manuscript was written in response to an article by Yosef Haim Brenner staunchly criticizing Judaism, and was apparently meant to be included in the article “Ha’Arachat Atzmenu,” but was censored and is now being published here for the very first time.The article “Ha’Arachat Atzmenu” was not published during Gordon's lifetime but rather later – in Kitvei A.D. Gordon [A.D. Gordon's Writings], edited by Yosef Aharonovich, editor of Ha-Po‘el Ha-tsa‘ir [The Young Worker] political party’s publisher. Now that parts of the manuscript were found at Yael Gordon’s archive, it turns out that Aharonovich removed sections and phrases from Gordon’s writings that were “too Jewish” or overly critical of Christianity and other spiritual beliefs common in the West.It is already well known that A.D. Gordon loved the religion of Israel and observed the Sabbath and holidays as per the Halachah, although from a certain point onward, he stopped praying and lived among secular Jews. Moreover, it is well known that he believed that hostility toward the religion of Israel among the Zionist Movement is a danger to the manifestation and realization of its goals. However, now, from within the censored section, yet another deeper level of Gordon's attitude toward religion is revealed, as well as how this attitude was incorporated into his worldview and philosophy. The sequence of sections from “Ha’Arachat Atzmenu” presents – in accordance with the Hebrew Bible, Midrash, and Kabbalah, and unlike non-Jewish theological stance – the perception that there can never be one overall religion for the whole of humanity (this claim does not contradict the longing for the End of Days, when all peoples shall thank God, and He will pass judgement upon them). To Gordon’s understanding, all historic religions were and will be national in essence. The essence of the individual who belongs to a nation is woven into the essence of the nation to which they belong. Therefore, no national movement, and certainly not Zionism – due to which the people of Israel have returned to the Land of Israel – shall be realized or realize itself and its goals without positive sentiments toward its people’s historic religion, as well as good relations between those who follow the nation’s historic religion and those who do not.
Keywords: A.D. Gordon; Religion and Nationalism; the Religion of Israel; Yael Gordon; Religion Sentiment